Adherence to prescribed antihypertensive medication among patients with depression in the United States - Quanjun Liu; Haochen Wang; Anbang Liu; Cheng Jiang; Weiya Li; Huan Ma; Qingshan Geng (BMC Psychiatry, 2022)
Abstract Background Hypertensive patients with depression have a higher mortality rate and a worse prognosis compared with hypertensive only. Depression may reduce medication adherence in hypertension patients. Methods This study includes respondents in the National Health and Nutritional Examination Survey (NHANES) database from 2005 to 2018 who had previously been diagnosed with hypertension. Medication adherence was defined as taking medication as recommended by a physician. The depressive state was assessed using the patient health questionnaire (PHQ)-9. Results Nine thousand one hundred eighty-six respondents were included in the analysis. Medication adherence was associated with depression (odds ratio [OR]: 1.48, 95% confidence interval [CI]: 1.26 to1.75) and depression score (OR: 1.04 per each point increase, 1.03 to 1.05) in the unadjusted analyses. After adjusting for clinical and socioeconomic/demographic factors, there were significant statistical correlations between depression score and medication adherence (aOR: 1.02 per each point increase, 1.00 to 1.03, p < 0.05), but there was no significant statistical correlation between depression and medication adherence (p > 0.05). It was still statistically significant relationships between sex, age, body mass index (BMI), race, marital status, and health insurance with medication adherence after adjusted socioeconomic/demographic factors. Conclusion Depression was marginally associated with poor medication adherence in hypertensive patients, and the correlation increased with depression degree. Moreover, socioeconomic/demographic factors have an independent impact on medication adherence including sex, age, BMI, race, marital status, and health insurance.